A wear-resistant anti-fouling skin glaze ceramic tile and a preparation method thereof

CN123003145APending Publication Date: 2026-10-30GUANGDONG HOMEWAY CERAMICS IND +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611167385.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提出一种耐磨防污肌肤釉陶瓷砖及其制备方法,以解决上述肌肤釉无法兼顾柔滑触感与耐磨防污性能的问题

Benefits of technology

所述耐磨防污肌肤釉陶瓷砖采用“肌肤质感底釉层—哑光精雕墨水层—高耐磨肌肤釉层”的三层复合结构,通过优化调整底釉的配方,使釉面具备温润如玉的肌肤质感;再通过向效果釉引入高铝增强组分,形成耐磨防污层,既保证了柔滑触感,又显著提升了表面的耐磨等级和防污等级,实现了肌肤质感与耐磨防污性能的有效兼顾,从而缓解了传统肌肤釉瓷砖过度依赖表层效果釉提供肌肤质感的技术局限。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003145A_ABST
    Figure CN123003145A_ABST
Patent Text Reader

Abstract

The application discloses a wear-resistant and stain-resistant skin glaze ceramic tile and a preparation method thereof. The wear-resistant and stain-resistant skin glaze ceramic tile comprises a body, a bottom glaze layer, a pattern layer and an effect glaze layer which are sequentially stacked from bottom to top. The wear-resistant and stain-resistant skin glaze ceramic tile adopts a three-layer composite structure of a skin texture bottom glaze layer, a matte fine carving ink layer and a high wear-resistant skin glaze layer. The formula of the bottom glaze is optimized and adjusted, so that the glaze surface has a skin texture of being as soft as jade. High-aluminum reinforcing components are introduced into the effect glaze to form a wear-resistant and stain-resistant layer, so that the smooth touch is ensured, the wear-resistant grade and the stain-resistant grade of the surface are significantly improved, the skin texture and the wear-resistant and stain-resistant performance are effectively considered, and the technical limitation that a traditional skin glaze ceramic tile excessively depends on a surface effect glaze to provide the skin texture is relieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ceramic technology, and in particular to a wear-resistant and stain-resistant skin-glaze ceramic tile and its preparation method. Background Technology

[0002] With social development and the continuous improvement of people's living standards, the requirements for the gloss and tactile feel of ceramic tile decorations are constantly increasing. Skin-like glaze products are favored by the market because of their delicate and smooth surface, warm and jade-like touch, and texture similar to a baby's skin.

[0003] However, to achieve a silky, skin-friendly texture, skin-glaze ceramic tile products on the market typically use glaze formulas with low melting points, high glass phase content, and low aluminum content. However, due to the high glass phase content and low crystalline phase content, the overall Mohs hardness of the glaze surface is relatively low, resulting in poor wear resistance. After long-term use in high-traffic areas, the glaze surface is prone to scratches and even wear down decorative patterns, significantly limiting the application and promotion of skin-glaze ceramic tiles in the flooring sector.

[0004] Furthermore, while the glaze surface formed by existing low-melting-point, high-glass-phase glaze formulations is smooth, the glaze layer contains numerous microscopic pores and incompletely melted areas. In daily use, it easily absorbs colored contaminants such as tea stains, coffee, and oil stains. Moreover, due to the low hardness and poor wear resistance of the glaze, micro-scratches on the surface further exacerbate the penetration and retention of stains, causing the tiles to gradually yellow or develop discoloration during use, affecting the durability and aesthetics of the decorative effect. Summary of the Invention

[0005] The purpose of this invention is to propose a wear-resistant and stain-resistant skin-like glaze ceramic tile and its preparation method, so as to solve the problem that the above-mentioned skin-like glaze cannot simultaneously achieve a smooth touch and wear-resistant and stain-resistant performance.

[0006] To achieve this objective, the present invention adopts the following technical solution: This invention provides a wear-resistant and stain-resistant skin-like glaze ceramic tile, comprising a body, a base glaze layer, a pattern layer, and an effect glaze layer stacked sequentially from bottom to top; The raw materials for preparing the base glaze layer include the following components in parts by weight: 30-55 parts potassium feldspar, 5-10 parts kaolin, 10-30 parts quartz, 5-12 parts alumina, 8-12 parts zirconium silicate, 5-10 parts dolomite, and 1-5 parts calcined talc. The raw materials for preparing the effect glaze layer include the following components in parts by weight: 20-30 parts of sodium feldspar, 20-30 parts of potassium feldspar, 5-10 parts of kaolin, 10-20 parts of barium carbonate, 8-12 parts of dolomite, 3-6 parts of zinc oxide, and 14-23 parts of high-alumina reinforcing components.

[0007] In the wear-resistant and stain-resistant skin-like glaze ceramic tile, the high-alumina reinforcing component includes 4-8 parts of corundum micro powder and 10-15 parts of high-alumina frit.

[0008] In the wear-resistant and stain-resistant skin-like glaze ceramic tile, the particle size of the corundum micro powder is 20-40 μm.

[0009] In the wear-resistant and stain-resistant skin-like glaze ceramic tile, the raw materials for preparing the base glaze layer include the following chemical components by mass percentage: SiO2 60-68%, Al2O3 15-23%, Fe2O3 0.1-0.6%, K2O 3.5-5.6%, CaO 1.5-3.5%, MgO 0.5-2.1%, Na2O 0.8-2.5%, TiO2 0-0.1%, ZrO 5-11%, and loss on ignition 0-9%.

[0010] In the wear-resistant and stain-resistant skin-like glaze ceramic tile, the raw materials for preparing the effect glaze layer include the following chemical components by mass percentage: SiO2 45-51%, Al2O3 19-26%, Fe2O3 0.3-1%, CaO 3-8%, MgO 1-3.2%, K2O 2.3-5.5%, Na2O 3.2-4.6%, TiO2 0-0.3%, BaO 5-10%, ZnO 4-6.2%, and loss on ignition 5-7%.

[0011] This invention also provides a method for preparing wear-resistant and stain-resistant skin-like glaze ceramic tiles, which includes the following steps: S1: Press the green body and dry it; then apply a base glaze to the green body and dry it to form a base glaze layer on the green body, thus obtaining brick body A; S2: Print ceramic ink on the surface of the base glaze layer of brick A to form a pattern layer on the base glaze layer, thus obtaining brick B; S3: Spray effect glaze onto brick body B and dry it to form an effect glaze layer on the pattern layer, thus obtaining brick body C; S4: High-temperature firing of brick body C yields wear-resistant and stain-resistant skin-glazed ceramic tiles; S5: The ceramic tile is brushed and polished to obtain a wear-resistant and stain-resistant skin-glazed ceramic tile.

[0012] In the preparation method of the wear-resistant and stain-resistant skin-like glaze ceramic tile, in step S1, the specific gravity of the base glaze is 1.86–1.92 g / cm³. 3 Glazing amount is 550-610g / m² 2 .

[0013] In the preparation method of the wear-resistant and stain-resistant skin-like glaze ceramic tile, in step S2, before printing the ceramic ink, the temperature of the tile body A is maintained at 35-45℃; the ink volume of the digital mold ink is 10-110 g / m³. 2 .

[0014] In the preparation method of the wear-resistant and stain-resistant skin-like glaze ceramic tile, in step S3, the specific gravity of the effect glaze is 1.45-1.52 g / cm³. 3 Glazing amount is 300-355g / m² 2 .

[0015] In the preparation method of the wear-resistant and stain-resistant skin-glazed ceramic tile, in step S4, the high-temperature firing temperature is 1160-1170℃ and the high-temperature firing time is 60-70min.

[0016] One technical solution of the present invention can have the following beneficial effects: The wear-resistant and stain-resistant skin-like glaze ceramic tile adopts a three-layer composite structure of "skin-textured base glaze layer - matte fine-carved ink layer - highly wear-resistant skin-like glaze layer". By optimizing and adjusting the formula of the base glaze, the glaze surface has a warm and jade-like skin-like texture. Then, by introducing high-alumina reinforcing components into the effect glaze, a wear-resistant and stain-resistant layer is formed, which not only ensures a smooth touch, but also significantly improves the wear resistance and stain resistance of the surface. It achieves an effective balance between skin-like texture and wear-resistant and stain-resistant performance, thereby alleviating the technical limitations of traditional skin-like glaze ceramic tiles that rely too much on the surface effect glaze to provide a skin-like texture. Attached Figure Description

[0017] Figure 1 This is a cross-sectional view of one embodiment of the present invention; Figure 2 This describes the appearance of the wear-resistant and stain-resistant skin-glazed ceramic tile prepared in Example 1; Figure 3 This describes the appearance of the wear-resistant and stain-resistant skin-glazed ceramic tile prepared in Example 2; In the attached diagram: 1. Body, 2. Base glaze, 3. Pattern glaze, 4. Effect glaze. Detailed Implementation

[0018] The technical solution of the present invention will be further illustrated below through specific embodiments. To facilitate understanding of the present invention, a more comprehensive description is provided below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of the present invention.

[0019] Where specific techniques or conditions are not specified in the examples, they shall be performed in accordance with the techniques or conditions described in the literature in this field or in accordance with the product instructions. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0021] Please refer to Figures 1-3 The present invention provides a wear-resistant and stain-resistant skin-glazed ceramic tile, comprising a body 1, a base glaze layer 2, a pattern layer 3 and an effect glaze layer 4 stacked sequentially from bottom to top; The raw materials for preparing the base glaze layer 2 include the following components in parts by weight: 30-55 parts potassium feldspar, 5-10 parts kaolin, 10-30 parts quartz, 5-12 parts alumina, 8-12 parts zirconium silicate, 5-10 parts dolomite, and 1-5 parts calcined talc. The raw materials for preparing the effect glaze layer 4 include the following components in parts by weight: 20-30 parts of sodium feldspar, 20-30 parts of potassium feldspar, 5-10 parts of kaolin, 10-20 parts of barium carbonate, 8-12 parts of dolomite, 3-6 parts of zinc oxide, and 14-23 parts of high-alumina reinforcing components.

[0022] The silica-alumina molar ratio of the base glaze layer 2 is adjusted to 1:4.2 to 1:5.1. During firing, the base glaze produces a large number of nano-sized mullite whiskers, which interweave within the glass phase, constructing a rigid support substrate with a hardness of 6.5 GPa. The nano-sized mullite whiskers and the glass phase, together with the high-alumina reinforcing components in the effect glaze, form a eutectic glass phase at high temperature, exhibiting excellent wear resistance and reducing the possibility of scratches on the glaze surface, thereby improving the glaze's anti-fouling ability.

[0023] The wear-resistant and stain-resistant skin-like glaze ceramic tile adopts a three-layer composite structure of "skin-textured base glaze layer - matte fine-carved ink layer - highly wear-resistant skin-like glaze layer". By optimizing and adjusting the formula of the base glaze, the glaze surface has a warm and jade-like skin-like texture. Then, by introducing high-alumina reinforcing components into the effect glaze, a wear-resistant and stain-resistant layer is formed, which not only ensures a smooth touch, but also significantly improves the wear resistance and stain resistance of the surface. It achieves an effective balance between skin-like texture and wear-resistant and stain-resistant performance, thereby alleviating the technical limitations of traditional skin-like glaze ceramic tiles that rely too much on the surface effect glaze to provide a skin-like texture.

[0024] Specifically, the high-alumina reinforcing component comprises 4-8 parts of corundum micro powder and 10-15 parts of high-alumina frit.

[0025] The high-alumina reinforcing component includes high-alumina frit and corundum micropowder. During firing, the corundum micropowder particles form a dense structure with the glaze layer and can also induce the precipitation of high-hardness corundum microcrystals and mullite phases in the high-alumina frit. The corundum micropowder and the microcrystals precipitated in situ from the high-alumina frit form a multi-level strengthening effect, significantly improving the wear resistance of the glaze surface, with a wear resistance level of up to level 4 at 6000 revolutions.

[0026] The aluminum content of high-alumina frit is 23-26%. The chemical composition of high-alumina frit includes: 48-49% SiO2, 24-25% Al2O3, 0.2-0.3% Fe2O3, 17-18% CaO, 5.1-5.2% MgO, 2.0-2.1% K2O and 1.3-1.4% Na2O.

[0027] Specifically, the particle size of the corundum micro powder is 20–40 μm.

[0028] By using corundum micro powder with the above-mentioned particle size, the corundum micro powder can be evenly dispersed in the glaze layer and precipitated in the form of fine crystals. While improving the hardness of the glaze surface, it avoids the formation of bumps or rough touches on the glaze surface due to excessively large particles. Thus, while giving the glaze wear resistance, it maintains the delicate and smooth skin texture of the glaze, achieving an effective balance between wear resistance and touch.

[0029] Specifically, the raw materials for preparing the base glaze layer 2 include the following chemical components by mass percentage: SiO2 60-68%, Al2O3 15-23%, Fe2O3 0.1-0.6%, K2O 3.5-5.6%, CaO 1.5-3.5%, MgO 0.5-2.1%, Na2O 0.8-2.5%, TiO2 0-0.1%, ZrO 5-11%, and loss on ignition 0-9%.

[0030] The base glaze serves to cover the color of the ceramic body, enhance the color development of the ceramic ink, and match the coefficient of thermal expansion of the ceramic body. Furthermore, to give the tiles a warm and delicate skin-like texture, the composition of the base glaze is optimized: Potassium feldspar is an alkali metal aluminosilicate, used to introduce K₂O into the base glaze. Potassium feldspar begins to decompose and melt at 1130–1450℃ and has a relatively high viscosity.

[0031] Since potassium feldspar ore is often associated with sodium feldspar, and potassium feldspar also contains a small amount of Na2O, it will introduce Na2O into the base glaze. Na2O has a stronger fluxing effect than K2O, resulting in a glaze with better transparency after firing, but it can easily cause the base color of the body to show through, affecting the stability of the glaze color. Therefore, it is necessary to control the Na2O content.

[0032] Kaolin is used as a base glaze to introduce silica and alumina; quartz is used to introduce silica and alumina respectively; dolomite is used to introduce calcium oxide and magnesium oxide; and calcined talc is used to introduce calcium oxide. The main function of calcium oxide and magnesium oxide in the base glaze is as flux. At high temperatures, the microcrystals formed by the reaction of calcium oxide with aluminum and silicon, such as anorthite and wollastonite, give the glaze a soft feel and delicate texture. Furthermore, the microcrystals also have a matting effect, making the glaze's gloss even softer and warmer.

[0033] Magnesium oxide releases free oxygen in the base glaze at high temperatures, disrupting the network structure, reducing the viscosity of the glaze melt, and improving its fluidity, resulting in a smooth glaze surface. By partially replacing Na₂O and K₂O with calcium oxide and magnesium oxide as fluxes, the fine and smooth texture of the glaze surface can be improved while ensuring that the firing temperature of the formula does not fluctuate significantly within a large range.

[0034] In addition, zirconium silicate is added to the base glaze to enhance its opacifying effect.

[0035] Specifically, the raw materials for preparing the effect glaze layer 4 include the following chemical components by mass percentage: SiO2 45-51%, Al2O3 19-26%, Fe2O3 0.3-1%, CaO 3-8%, MgO 1-3.2%, K2O 2.3-5.5%, Na2O 3.2-4.6%, TiO2 0-0.3%, BaO 5-10%, ZnO 4-6.2%, and loss on ignition 5-7%.

[0036] To improve the hardness and wear resistance of the glaze, the composition of the effect glaze was optimized: In effect glazes, alumina acts as a network intermediate. Increasing the Al2O3 content in the effect glaze improves its hardness and wear resistance. Therefore, the effect glaze incorporates corundum micropowder to enhance its wear resistance. Corundum is a special crystal form of alumina, with a Mohs hardness of 9, second only to diamond, exhibiting extremely high wear resistance. Furthermore, it is heat-resistant and chemically stable at high temperatures.

[0037] However, excessive corundum can make the glaze rough and affect its texture. The aforementioned effect glaze also replaces some of the corundum by introducing high-alumina frit. The high-alumina frit has already completed the degassing process during pre-melting, significantly reducing gas release during subsequent firing, resulting in a smoother and denser glaze. Furthermore, the high-alumina frit melts earlier and more completely, allowing for more thorough melting and better leveling of the glaze slurry, which is beneficial for forming a smooth and dense glaze surface. During firing, the high-alumina frit remelts, uniformly releasing the aluminum component. The grains are fine and evenly distributed, resulting in a denser and more uniform microstructure of the glaze, making the glaze texture more delicate.

[0038] The effect glaze also contains barium carbonate, which helps to develop the color of ceramic inks. Using the above-mentioned amount of barium carbonate, barium feldspar crystals can be precipitated on the glaze surface during firing, reducing the gloss of the glaze and making the light feel softer. Compared with high-temperature matte glaze, crystalline matte glaze has a more delicate and smooth feel.

[0039] This invention also provides a method for preparing wear-resistant and stain-resistant skin-like glaze ceramic tiles, which includes the following steps: S1: Press the green body and dry it; then apply a base glaze to the green body and dry it to form a base glaze layer 2 on the green body 1, thus obtaining brick body A; S2: Print ceramic ink on the surface of the base glaze layer 2 of brick body A to form a pattern layer 3 on the base glaze layer 2, thus obtaining brick body B; S3: Spray effect glaze onto brick body B and dry it to form effect glaze layer 4 on pattern layer 3, thus obtaining brick body C; S4: High-temperature firing of brick body C yields wear-resistant and stain-resistant skin-glazed ceramic tiles; S5: The ceramic tile is brushed and polished to obtain a wear-resistant and stain-resistant skin-glazed ceramic tile.

[0040] The ceramic ink is specifically a matte engraving ink. During the firing process, the matte micro-engraving ink undergoes a gradient diffusion reaction with the base glaze and effect glaze, forming semi-embedded matte texture units with a depth of 2-5 μm. These semi-embedded matte texture units break the uniform structure of the traditional single-glaze continuous reflective interface, changing the glaze reflection from mainly specular reflection to mainly diffuse reflection. This reduces the uniformity fluctuation of the glaze gloss, resulting in a soft and even luster, and visually presenting a delicate and smooth skin texture.

[0041] The preparation steps of the base glaze include: weighing the raw materials according to the formula, adding water, and ball milling. The fineness of the glaze slurry after ball milling is controlled so that the mass percentage of residue on a 325-mesh sieve is 0.3%–0.5%, and the mass percentage of water in the glaze slurry is 28%–32%. After passing the ball milling, the slurry is discharged, sieved, iron removed, homogenized, and aged to obtain the base glaze. The preparation steps of the effect glaze are the same as those of the base glaze and will not be described in detail here.

[0042] In this invention, there are no restrictions on the composition of the blank. The blank can be a ceramic or stone brick made of clay or sand as the main raw material.

[0043] Specifically, in step S1, the specific gravity of the base glaze is 1.86–1.92 g / cm³. 3 Glazing amount is 550-610g / m² 2 .

[0044] By limiting the specific gravity of the base glaze to 1.86–1.92 g / cm³ 3This ensures that the base glaze has suitable suspension stability and leveling properties, allowing it to spread evenly on the brick surface. This avoids problems such as excessively thick glaze layers and cracking due to excessively high specific gravity, or uneven coverage and insufficient hiding power due to excessively low specific gravity. At the same time, controlling the amount of glaze application ensures that the base glaze forms a moderately thick and dense base glaze layer 2, effectively covering the base color of the brick body. This provides a smooth and dense adhesion base for the subsequent application of effect glazes, which is beneficial to improving the overall stability of the glaze quality.

[0045] Specifically, in step S2, before printing the ceramic ink, the temperature of the brick body A is maintained at 35–45°C; the ink volume of the digital mold ink is 10–110 g / m³. 2 .

[0046] Pattern designs and textures can be formed by inkjet printing with matte engraving ink. The engraving depth can be precisely controlled by adjusting the amount of matte engraving ink, resulting in a strong three-dimensional sense of texture, natural and beautiful transitions, and effectively enhancing the decorative appeal of the product.

[0047] Specifically, in step S3, the specific gravity of the effect glaze is 1.45–1.52 g / cm³. 3 Glazing amount is 300-355g / m² 2 .

[0048] Matte engraving inks are inherently water-repellent. This is achieved by lowering the specific gravity of the effect glaze to 1.45–1.52 g / cm³. 3 The proportion of liquid phase medium in the glaze increases relatively, and the difference in interfacial tension between it and the hydrophobic carving ink becomes more significant, thereby enhancing the repulsive effect and forming a deeper and more realistic texture carving effect in the contact area between the two phases.

[0049] Specifically, in step S4, the high-temperature firing temperature is 1160-1170℃, and the high-temperature firing time is 60-70 minutes.

[0050] Example 1 A method for preparing a wear-resistant and stain-resistant skin-like glaze ceramic tile includes the following steps: S1: Press the green body and dry it at 185℃ for 67 minutes; then apply a base glaze to the green body and dry it in the glaze line; the specific gravity of the base glaze is 1.90 g / cm³. 3 Glazing amount is 600g / m 2 A base glaze layer 2 is formed on the blank 1 to obtain brick body A; S2: Maintain brick body A temperature at 35℃, print matte engraving ink and design pattern, the ink volume of the digital mold ink is 10g / m³. 2 Brick B is obtained; S3: Spray effect glaze onto brick body B. The specific gravity of the effect glaze is 1.5 g / cm³. 3 Glazing amount is 350g / m 2 Then, it enters the glaze line for drying, forming an effect glaze layer 4 on the pattern layer 3, thus obtaining the brick body C; S4: The brick body C is fired at high temperature, with a firing temperature of 1166℃ and a firing time of 65min, to obtain wear-resistant and stain-resistant skin-glazed ceramic tiles; S5: Polish the ceramic tile to obtain a wear-resistant, stain-resistant, skin-friendly glaze ceramic tile; The base glaze formula includes the following components by weight: 42 parts potassium feldspar, 8 parts kaolin, 22 parts quartz, 8 parts alumina, 10 parts zirconium silicate, 6 parts dolomite, and 4 parts calcined talc.

[0051] The chemical composition of the base glaze is: 60.07% SiO2, 20.31% Al2O3, 0.21% Fe2O3, 3.89% K2O, 2.31% CaO, 1.96% MgO, 1.08% Na2O, 0.07% TiO2, 6.49% ZrO and 3.61% loss on ignition.

[0052] The raw materials for the effect glaze include the following components by weight: 24 parts potassium feldspar, 22 parts sodium feldspar, 8 parts kaolin, 15 parts barium carbonate, 8 parts dolomite, 6 parts corundum powder, 12 parts high-alumina frit, and 5 parts zinc oxide. The chemical composition of the high-alumina frit includes: 48.51% SiO2, 24.83% Al2O3, 0.25% Fe2O3, 17.85% CaO, 5.16% MgO, 2.02% K2O, and 1.38% Na2O.

[0053] The chemical composition of the effect glaze is: 47.43% SiO2, 19.72% Al2O3, 0.4% Fe2O3, 0.1% TiO2, 1.58% MgO, 2.78% K2O, 5.38% CaO, 3.53% Na2O, 8.69% BaO, 4.96% ZnO and 5.43% loss on ignition.

[0054] Example 2 The specific steps of Example 2 are basically the same as those of Example 1, except that: in step S1, the drying temperature is 180℃ and the drying time is 65 min; the specific gravity of the base glaze is 1.86 g / cm³. 3 Glazing amount is 610g / m 2 In step S2, the temperature of brick A is maintained at 40°C; the ink volume of the digital mold ink is 110 g / m³. 2 In step S3, the specific gravity of the effect glaze is 1.51 g / cm³. 3 Glazing amount is 345g / m 2In step S4, the high-temperature firing temperature is 1160℃ and the high-temperature firing time is 70min.

[0055] The base glaze formula includes the following components by weight: 30 parts potassium feldspar, 10 parts kaolin, 30 parts quartz, 5 parts alumina, 8 parts zirconium silicate, 5 parts dolomite, and 1 part calcined talc.

[0056] The raw materials of the effect glaze include the following components by weight: 20 parts potassium feldspar, 28.5 parts sodium feldspar, 10 parts kaolin, 10 parts barium carbonate, 12 parts dolomite, 8 parts corundum powder, 10 parts high-alumina frit, and 4.5 parts zinc oxide.

[0057] Comparative Example 1 The specific steps of Comparative Example 1 are the same as those of Example 1, except that corundum micro powder is removed from the effect glaze formula and replaced with potassium feldspar in equal parts by mass. The effect glaze of Comparative Example 1 includes 30 parts potassium feldspar, 22 parts sodium feldspar, 8 parts kaolin, 15 parts barium carbonate, 8 parts dolomite, 12 parts high alumina frit and 5 parts zinc oxide.

[0058] Comparative Example 2 The specific steps of Comparative Example 2 are the same as those of Example 1, except that the high-alumina frit is removed from the effect glaze formula and replaced with an equal amount of sodium feldspar. The effect glaze of Comparative Example 2 includes 24 parts potassium feldspar, 34 parts sodium feldspar, 8 parts kaolin, 15 parts barium carbonate, 8 parts dolomite, 6 parts corundum powder, and 5 parts zinc oxide.

[0059] Comparative Example 3 The specific steps of Comparative Example 2 are the same as those of Example 1, except that the base glaze is replaced with a conventional skin-like base glaze formula, which includes 45 parts of albite, 25 parts of quartz, 12 parts of calcite, 10 parts of kaolin, and 8 parts of zirconium silicate.

[0060] The skin-glazed ceramic tiles of Examples 1, 2, and Comparative Examples 1-3 were tested for wear resistance, Mohs hardness, stain resistance, water absorption, breaking strength, and skin texture evaluation. The results are shown in Table 1. The skin texture evaluation test was conducted by the same person using the same force to linearly slide the sample surface. This test was used to assist in determining the skin feel effect, and a 5-point scoring system was used, with 1 point being the lowest score.

[0061] Table 1 - Test Results

[0062] Compared to Examples 1 and 2, in Comparative Example 1, the removal of corundum micropowder resulted in a decrease in abrasion resistance revolutions, a reduction in Mohs hardness, and a drop in the stain resistance rating from 5 to 3. This indicates that corundum micropowder, as a high-hardness crystalline phase, is a key component in improving the abrasion resistance and Mohs hardness of the glaze. In Comparative Example 2, the removal of the high-alumina frit resulted in a decrease in abrasion resistance revolutions to 1600 revolutions, a drop in Mohs hardness to 5, a drop in the stain resistance rating to 4, and a decrease in the skin-feel evaluation. Comparative Examples 1 and 2 demonstrate that a combination of corundum micropowder and high-alumina frit is necessary to achieve good abrasion resistance and stain resistance. In Comparative Example 3, replacing the base glaze with a conventional albite system resulted in abrasion resistance revolutions, Mohs hardness, and stain resistance rating that were essentially the same as in Example 1, but the skin-feel evaluation decreased, with a rougher texture and a lack of warmth.

[0063] The technical principles of the present invention have been described above with reference to specific embodiments. These descriptions are merely for explaining the principles of the invention and should not be construed as limiting the scope of protection of the invention in any way. Based on this explanation, those skilled in the art can readily conceive of other specific embodiments of the invention without inventive effort, and these equivalent variations or substitutions are all included within the scope defined by the claims of this application.

Claims

1. A wear-resistant and stain-resistant skin-like glaze ceramic tile, characterized in that, It includes the body, base glaze layer, pattern layer and effect glaze layer, which are stacked in sequence from bottom to top; The raw materials for preparing the base glaze layer include the following components in parts by weight: 30-55 parts potassium feldspar, 5-10 parts kaolin, 10-30 parts quartz, 5-12 parts alumina, 8-12 parts zirconium silicate, 5-10 parts dolomite, and 1-5 parts calcined talc. The raw materials for preparing the effect glaze layer include the following components in parts by weight: 20-30 parts of sodium feldspar, 20-30 parts of potassium feldspar, 5-10 parts of kaolin, 10-20 parts of barium carbonate, 8-12 parts of dolomite, 3-6 parts of zinc oxide, and 14-23 parts of high-alumina reinforcing components.

2. The wear-resistant and stain-resistant skin-like glaze ceramic tile according to claim 1, characterized in that, The high-alumina reinforcing component comprises 4-8 parts of corundum micro powder and 10-15 parts of high-alumina frit.

3. The wear-resistant and stain-resistant skin-glaze ceramic tile according to claim 1, characterized in that, The particle size of the corundum micro powder is 20–40 μm.

4. The wear-resistant and stain-resistant skin-glaze ceramic tile according to claim 1, characterized in that, The raw materials for preparing the base glaze layer include the following chemical components by mass percentage: SiO2 60-68%, Al2O3 15-23%, Fe2O3 0.1-0.6%, K2O 3.5-5.6%, CaO 1.5-3.5%, MgO 0.5-2.1%, Na2O 0.8-2.5%, TiO2 0-0.1%, ZrO 5-11%, and loss on ignition 0-9%.

5. The wear-resistant and stain-resistant skin-like glaze ceramic tile according to claim 1, characterized in that, The raw materials for preparing the effect glaze layer include the following chemical components by mass percentage: SiO2 45-51%, Al2O3 19-26%, Fe2O3 0.3-1%, CaO 3-8%, MgO 1-3.2%, K2O 2.3-5.5%, Na2O 3.2-4.6%, TiO2 0-0.3%, BaO 5-10%, ZnO 4-6.2%, and loss on ignition 5-7%.

6. A method for preparing a wear-resistant and stain-resistant skin-like glaze ceramic tile, characterized in that, The method for preparing the wear-resistant and stain-resistant skin-glaze ceramic tile according to any one of claims 1 to 5 includes the following steps: S1: Press the green body and dry it; then apply a base glaze to the green body and dry it to form a base glaze layer on the green body, thus obtaining brick body A; S2: Print ceramic ink on the surface of the base glaze layer of brick A to form a pattern layer on the base glaze layer, thus obtaining brick B; S3: Spray effect glaze onto brick body B and dry it to form an effect glaze layer on the pattern layer, thus obtaining brick body C; S4: High-temperature firing of brick body C yields wear-resistant and stain-resistant skin-glazed ceramic tiles; S5: The ceramic tile is brushed and polished to obtain a wear-resistant and stain-resistant skin-glazed ceramic tile.

7. The method for preparing a wear-resistant and stain-resistant skin-like glaze ceramic tile according to claim 6, characterized in that, In step S1, the specific gravity of the base glaze is 1.86–1.92 g / cm³. 3 Glazing amount is 550-610g / m² 2 .

8. The method for preparing a wear-resistant and stain-resistant skin-like glaze ceramic tile according to claim 6, characterized in that, In step S2, before printing the ceramic ink, the temperature of the brick body A is maintained at 35-45°C; the ink volume of the digital mold ink is 10-110 g / m³. 2 .

9. The method for preparing a wear-resistant and stain-resistant skin-like glaze ceramic tile according to claim 6, characterized in that, In step S3, the specific gravity of the effect glaze is 1.45–1.52 g / cm³. 3 Glazing amount is 300-355g / m² 2 .

10. The method for preparing a wear-resistant and stain-resistant skin-like glaze ceramic tile according to claim 6, characterized in that, In step S4, the high-temperature firing temperature is 1160-1170℃, and the high-temperature firing time is 60-70 minutes.